Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderating (Studi pada Perusahaan Manufaktur yang terdaftar di BEI): Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderating (Studi pada Perusahaan Manufaktur yang terdaftar di BEI) - Ningsih, Heny Triastuti Kurnia (JURNAL MUTIARA AKUNTANSI, 2017)
This research aims to examine the relationship between Corporate Social Responsibility and Profitability Ratios partially and simultaneously the Company Value and Profitability Ratios To determine whether moderate the Corporate Social Responsibility of the value of companies listed on the Indonesia Stock Exchange. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange as many as 136 companies. The sampling method in this study using purposive sampling method by 88 companies. Data collection methods used in this research is the method of documentation. The data were analyzed using linear regression, and partial uj on Regressioan Analysis Multiple methods previously have fulfilled classical assumption test. The results showed that no significant influences of Corporate Social Responsibility to the Value Manufacturing Company listed on the Indonesia Stock Exchange. There is a significant influence on Return On Equity to Value Manufacturing Company listed on the Indonesia Stock Exchange and profitability ratio (ROE) is not a variable that is able to moderate the Corporate Social Responsibility of the value of companies listed on the Indonesia Stock Exchange.Keywords: Corporate Social Responsibility, Return On Equity, Corporate Values